2015
DOI: 10.1177/2055102915601581
|View full text |Cite
|
Sign up to set email alerts
|

The role of Aboriginal community attachment in promoting lifestyle changes after hepatitis C diagnosis

Abstract: This research assessed whether greater attachment to an Aboriginal community buffers against the negative effects of stigma and promotes positive health outcomes. Aboriginal Australians (n = 203) living with hepatitis C completed a survey assessing community attachment, stigma, resilience, quality of life, treatment intent, hepatitis C knowledge and positive lifestyle changes. A stronger sense of community attachment was associated with greater resilience, increased quality of life, less hepatitis C–related st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Acknowledging the colonial context in BC, the perspectives of Indigenous Peoples in this study sample, and the harmful clinical encounters described herein, findings from this study also align with a growing body of Canadian and international empirical evidence highlighting how HCVaffected Indigenous Peoples are distinctly and inequitably mistreated within healthcare settings (26,(71)(72)(73). For Indigenous Peoples, including those who use substances and who face substance use stigma, historical and ongoing contexts of systemic racism and colonialism are known to create barriers to safe, effective, and timely healthcare (57,74).…”
Section: Discussionsupporting
confidence: 71%
“…Acknowledging the colonial context in BC, the perspectives of Indigenous Peoples in this study sample, and the harmful clinical encounters described herein, findings from this study also align with a growing body of Canadian and international empirical evidence highlighting how HCVaffected Indigenous Peoples are distinctly and inequitably mistreated within healthcare settings (26,(71)(72)(73). For Indigenous Peoples, including those who use substances and who face substance use stigma, historical and ongoing contexts of systemic racism and colonialism are known to create barriers to safe, effective, and timely healthcare (57,74).…”
Section: Discussionsupporting
confidence: 71%
“…19 Responses from the Likert scale were transformed into dichotomous variables, namely 'Disagree' (grouping together the first three responses, Strongly Disagree, Disagree, and Neutral) and 'Agree' (the last two responses, Agree and Strongly Agree); the response 'Neutral' was included in the first group. This scoring system was adopted from previous Australian studies 5,20,21 that measured HCV treatment intention and suggested that 'Neutral' did not necessarily mean 'Agree'. 'Disagree' and 'Agree' were recategorised into 'No' and 'Yes' respectively.…”
Section: Treatment Intentionmentioning
confidence: 99%
“…4 In addition, poverty, homelessness and mental health issues may be associated with a higher prevalence of HCV among Aboriginal people compared with non-Aboriginal people. 5 Cultural respect is a key element for ensuring Aboriginal people receive effective primary care, and this includes an understanding of the social determinants of health, as well as how individuals communicate their health needs, and developing services that are culturally responsive so as to achieve the most optimal care outcomes. 6 Australia has been at the forefront of HCV elimination globally.…”
Section: Introductionmentioning
confidence: 99%
“…A measure of attachment to a community of PWID adapted from Brener et al, 2013 , Brener et al, 2015 consisted of four items assessing how much the respondent felt they were part of a PWID community, how many of their friends inject drugs, how much of their free time is spent with PWID, and how much of their time is spent helping other PWID. Responses were scored on a 5-point measure and summed to create a scale (range 4–20, α = 0.77); higher scores indicative of a greater sense of PWID community attachment.…”
Section: Methodsmentioning
confidence: 99%